A free radical-based p-type doped organic semiconductor film and its preparation method and application
By adding free radical initiator and stabilizer to the organic semiconductor solution, a free radical p-type doped organic semiconductor thin film is prepared, which solves the problem of poor film stability in the prior art, and achieves efficient charge transport and improvement of perovskite solar cell performance.
Patent Information
- Application Number
- CN202211126867.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-16
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-09-16
AI Technical Summary
In the prior art, the p-type organic semiconductor film has poor long-term stability, the doping process takes a long time and has poor repeatability, and the doped film has a large number of by-products, which affects the stability.
A free radical initiator and a stabilizer are used to mix in an organic semiconductor solution, and a free radical p-type doped organic semiconductor thin film is prepared by spin coating, scraping coating or slit coating.
The conductivity and charge transfer capability of organic semiconductor thin films are significantly improved, the long-term stability of the thin films is enhanced, and the photoelectric conversion efficiency and stability of perovskite solar cells are improved.
Smart Images

Figure CN115425157B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic semiconductors, and in particular relates to a free radical-based p-type doped organic semiconductor film and a preparation method and application thereof. Background Art
[0002] Organic semiconductors have the advantages of good mechanical flexibility, light weight, and easy low-temperature processing. However, their intrinsic carrier mobility and conductivity are very low, which cannot meet the conductivity requirements of high-efficiency devices. P-type doping is the key to improving the optoelectronic performance of organic semiconductors. It can accurately adjust the position of the Fermi level relative to the semiconductor transport energy level, control the energy barrier of charge injection, and increase effective charge transfer.
[0003] The traditional method of p-type doping organic semiconductors based on lithium salts / oxygen involves a complex two-step reaction. Taking spiro-OMeTAD as an example, the lithium salt-doped spiro-OMeTAD film needs to be exposed to air to undergo an oxidation reaction with oxygen in the air to generate spiro-OMeTAD. ·+ O2 ·- , then, O2 ·- Spontaneous anion exchange with LiTFSI drives the reaction forward. Eventually, a large amount of lithium oxide Li x O y and oxidized spiro-OMeTAD ·+ TFSI - . This oxidation reaction is very slow and heavily dependent on the oxygen content in the environment, requiring 24 hours or even longer to proceed. In addition, since it needs to be exposed to air, changes in water, oxygen, and light in the air can easily affect the p-type doping process, and repeatability is difficult to control. Therefore, traditional dopant-doped p-type organic semiconductors have problems such as a long doping process, poor repeatability, and failure to meet the requirements of mass production. More importantly, the doped film contains a large amount of dopant byproducts, and the long-term stability of the film is poor. Summary of the invention
[0004] The purpose of the present invention is to overcome the above technical deficiencies, provide a free radical-based p-type doped organic semiconductor film and its preparation method and application, and solve the technical problem of poor long-term stability of p-type organic semiconductor films in the prior art.
[0005] In order to achieve the above technical purpose, the technical solution of the present invention is as follows:
[0006] In a first aspect, the present invention provides a method for preparing a free radical p-type doped organic semiconductor film, comprising the following steps:
[0007] Adding a free radical initiator and a stabilizer to the first organic semiconductor solution in sequence and mixing them evenly to obtain a second organic semiconductor solution; wherein the first organic semiconductor solution is obtained by dissolving a p-type organic semiconductor in a chlorinated organic solvent;
[0008] The second organic semiconductor solution is coated on the substrate and dried to form a film, thereby obtaining a free radical-based p-type doped organic semiconductor thin film.
[0009] Furthermore, the free radical initiator is benzoyl peroxide or azobisisobutyronitrile.
[0010] Furthermore, the amount of the free radical initiator added is 5 to 120 mol % relative to the p-type organic semiconductor.
[0011] Furthermore, the p-type organic semiconductor is spiro-OMeTAD, P3HT, PTAA or poly-TPD.
[0012] Furthermore, the chlorinated organic solvent is tetrachloroethane or pentachloroethane.
[0013] Further, the stabilizer includes tetrabutylammonium salt or butyl-3-methylimidazolium salt.
[0014] Furthermore, the tetrabutylammonium salt is tetrabutylammonium chloride, tetrabutylammonium perchlorate, tetrabutylammonium tetrafluoroborate, tetrabutylammonium hexafluorophosphate or tetrabutylammonium bistrifluoromethanesulfonimide.
[0015] Furthermore, the butyl-3-methylimidazolium salt is 1-butyl-3-methylimidazolium hexafluorophosphate or 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0016] Furthermore, the amount of the stabilizer added is 5 to 120 mol % relative to the p-type organic semiconductor.
[0017] Furthermore, the coating method is spin coating, blade coating or slit coating.
[0018] In a second aspect, the present invention provides a free radical-based p-type doped organic semiconductor film.
[0019] Furthermore, the thickness of the free radical-based p-type doped organic semiconductor film is between 70 and 200 nm.
[0020] In a third aspect, the present invention provides a perovskite solar cell, the device structure of which is a negative electrode, an electron transport layer, a perovskite layer, a hole transport layer and a positive electrode arranged in sequence, and the above-mentioned free radical-based p-type doped organic semiconductor film is used as the hole transport layer.
[0021] Compared with the prior art, the beneficial effects of the present invention include:
[0022] (1) The present invention explores a new idea for p-type doping of organic semiconductors. The doping process is simple and easy to operate, and an organic semiconductor film with ideal electrical properties and stability is prepared.
[0023] (2) The p-type doping method provided by the present invention increases the conductivity of the organic semiconductor film by four orders of magnitude; and changes the energy band position of the organic semiconductor, thereby significantly improving the charge transfer capability.
[0024] (3) The organic semiconductor film obtained by the present invention is used to prepare perovskite solar cells, which can significantly improve the photoelectric conversion efficiency and long-term stability of the device, and is conducive to promotion to other semiconductor device fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The relationship between the conductivity of the free radical-doped spiro-OMeTAD and different tetrabutylammonium salt stabilizers in Example 1 of the present invention.
[0026] Figure 2 3 is a box plot of the battery efficiency distribution obtained in Example 2 of the present invention, wherein (a) is a box plot of the battery efficiency distribution of the hole transport layer doped with different contents of the free radical initiator in Example 2 of the present invention; (b) is a box plot of the battery efficiency distribution prepared by adding 90 mol % of the free radical initiator and then adding different contents of 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt as a stabilizer.
[0027] Figure 3 This is a current-voltage diagram of a perovskite solar cell prepared as a hole transport layer by free radical-doping spiro-OMeTAD and adding 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt as a stabilizer in Example 2 of the present invention.
[0028] Figure 4 This is a current-voltage diagram of a perovskite solar cell prepared as a hole transport layer by free radical-doping spiro-OMeTAD and adding tetrabutylammonium hexafluorophosphate as a stabilizer in Example 3 of the present invention.
[0029] Figure 5 This is an MPP tracking output diagram of the unpackaged perovskite solar cell at the maximum power point under the irradiation of an LED lamp simulating sunlight in Example 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] The present invention provides a free radical-based p-type doped organic semiconductor film and a preparation method thereof. The p-type dopant used in the method has the advantages of good solubility in an organic solvent, high doping efficiency, low cost, etc. The obtained organic semiconductor film is applied to the preparation of a high-stability perovskite solar cell, which can solve technical problems such as poor device repeatability and stability, and is conducive to promotion to other semiconductor device fields.
[0032] In a first aspect, the present invention provides a method for preparing a free radical p-type doped organic semiconductor film, comprising the following steps:
[0033] (1) adding a free radical initiator to an organic semiconductor solution A (a first organic semiconductor solution) and mixing them uniformly to obtain a solution B; the organic semiconductor solution A is obtained by dissolving an organic semiconductor raw material in a chlorinated organic solvent, and the concentration of the organic semiconductor solution A is between 20 and 60 mM and can be adjusted according to the desired film thickness;
[0034] (2) Subsequently, tetrabutylammonium salt or butyl-3-methylimidazolium salt is added to solution B as a stabilizer to obtain a stable p-type doped organic semiconductor solution C (a second organic semiconductor solution);
[0035] (3) removing excess solvent from the organic semiconductor solution C by spin coating, scraper coating, slit coating, etc., to obtain a free radical-based p-type doped organic semiconductor film.
[0036] Preferably, in step (1), the free radical initiator is any one of benzoyl peroxide or azobisisobutyronitrile.
[0037] Preferably, in step (1), the chlorinated organic solvent is any one of tetrachloroethane or pentachloroethane.
[0038] Preferably, in step (1), the molar ratio of the free radical initiator molecules to the doped organic semiconductor molecules is 0 to 120 mol %, more preferably 5 to 120 mol %, and even more preferably 30 to 100 mol %.
[0039] Preferably, the organic semiconductor in step (1) is any one of spiro-OMeTAD, P3HT, PTAA or poly-TPD p-type organic semiconductors.
[0040] Preferably, in step (2), the tetrabutylammonium salt is any one of tetrabutylammonium chloride (TBACl, [CH3(CH2)3]4NCl), tetrabutylammonium perchlorate (TBAClO4, [CH3(CH2)3]4NClO4), tetrabutylammonium tetrafluoroborate (TBABF4, [CH3(CH2)3]4NBF4), tetrabutylammonium hexafluorophosphate (TBAPF6, [CH3(CH2)3]4NPF6) or tetrabutylammonium bistrifluoromethanesulfonimide (TBATFSI, [CH3(CH2)3]4N[N(SO2CF3)2]).
[0041] Preferably, in step (2), the butyl-3-methylimidazolium salt is 1-butyl-3-methylimidazolium hexafluorophosphate (BMIMPF6, C8H 15 F6N2P) or 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonimide) (BMIMTFSI, C 10 H 15 F6N3O4S2).
[0042] Preferably, the molar ratio of the tetrabutylammonium salt stabilizer to the doped organic semiconductor molecules is 0-120 mol %, more preferably 5-90 mol %, and even more preferably 30-90 mol %.
[0043] Preferably, the molar ratio of the butyl-3-methylimidazolium salt stabilizer to the doped organic semiconductor molecules is 0-120 mol %, more preferably 5-90 mol %, and even more preferably 10-60 mol %.
[0044] In a second aspect, the present invention provides a doped organic semiconductor film prepared by spin coating, blade coating, slit coating and the like.
[0045] In a third aspect, the present invention provides a perovskite solar cell, the device structure of which is a negative electrode, an electron transport layer, a perovskite layer, a hole transport layer and a positive electrode arranged in sequence; the cell adopts the above-mentioned p-type doped organic semiconductor film as the hole transport layer.
[0046] Preferably, the thickness of the hole transport layer film is 70 to 200 nm, within which the performance of the obtained battery is not much different; the molar ratio of the free radical initiator molecules to the organic semiconductor molecules is 90 mol%, the molar ratio of the tetrabutylammonium salt molecules to the organic semiconductor molecules is 90 mol% or the molar ratio of the butyl-3-methylimidazolium salt molecules to the organic semiconductor molecules is 30 mol%; the battery negative electrode is ITO or FTO conductive glass; the battery electron transport layer is TiO2 or SnO2; the perovskite light absorption layer is MAPbI3, FAPbI3, FA 1-x MA x Pb(I1-y Br y 3. FA 1-x MA x Pb(I 1-y Br y )3. Cs x FA 1-x Pb(I 1-y Br y )3. Cs x FA 1- y MA y Pb(I 1-y Br y )3. Rb x Cs y FA 1-y Pb(I 1-z Br z )3, etc., wherein x=0~0.2, y=0~0.9, z=0~1, and at least one of x, y and z is not zero; the positive electrode of the battery is metal Au, Ag or Cu.
[0047] The main mechanism of action of the present invention:
[0048] The p-type doping method of the present invention is to add a free radical initiator to a chlorinated organic solution of an organic semiconductor and mix them evenly; then, tetrabutylammonium salt or butyl-3-methylimidazolium salt is added to the solution as a stabilizer to obtain a stable p-type doped organic semiconductor solution; in the present invention, the initiator needs to be added first and then the stabilizer, and the two have different functions, the initiator is added first to initiate the generation of organic semiconductor free radicals; then the stabilizer is added to obtain a more stable organic semiconductor free radical through anion exchange reaction. Finally, the stable p-type doped organic semiconductor solution is subjected to spin coating, scraping coating, slit coating and other methods to remove excess solvent therein to obtain a solid doped organic semiconductor film.
[0049] By doping organic semiconductors, electrons at the HOMO energy level of organic semiconductors transition to dopants, shifting their Fermi energy level toward the HOMO energy level, reducing the energy barrier for charge injection, increasing effective charge transfer, and improving conductivity and hole mobility. Applying doped films to perovskite solar cells can significantly improve the device's photoelectric conversion efficiency and stability under illumination.
[0050] The preferred free radical initiator, tetrabutylammonium salt and butyl-3-methylimidazolium salt doping agents of the present invention are low in cost and readily available, and the doping process is simple and easy to operate, which is conducive to promotion to other semiconductor device fields.
[0051] The following is a detailed description with reference to specific embodiments.
[0052] Example 1
[0053] The changes in the electrical conductivity of spiro-OMeTAD doped with different tetrabutylammonium salt-stabilized free radicals were investigated.
[0054] The conductivity of spiro-OMeTAD doped with different tetrabutylammonium salt-stabilized free radicals was tested using an interdigitated gold microelectrode array. The specific preparation method is as follows:
[0055] (1) Group 12: adding a free radical initiator to an organic semiconductor solution A, mixing well, and obtaining a solution B; adding a stabilizer TBACl to the solution B, and obtaining an organic semiconductor solution C;
[0056] The free radical initiator is benzoyl peroxide, the organic semiconductor solution A is obtained by dissolving the organic semiconductor spiro-OMeTAD in tetrachloroethane, and the added amount of benzoyl peroxide relative to spiro-OMeTAD is 90 mol%.
[0057] (2) The interdigitated gold microelectrode was cleaned with deionized water and anhydrous ethanol in turn, and then cleaned with ozone and placed in a glove box.
[0058] (3) In a nitrogen glove box, the organic semiconductor solution C obtained in step (1) (i.e., the prepared spiro-OMeTAD doping solution to which 90 mol % benzoyl peroxide and different tetrabutylammonium salt stabilizers are added) is spin-coated on the cleaned interdigitated gold microelectrode at a speed of 3000 rpm to obtain a spiro-OMeTAD film doped with different tetrabutylammonium salt-stabilized free radicals.
[0059] The device current-voltage relationship was tested using an electrochemical workstation, and the film conductivity was calculated using the formula σ=Id / V(2n-1)lh, where I is the test current, V is the applied voltage, n is the interdigit number, d is the distance between adjacent interdigits, l is the interdigit length, and h is the thickness of the hole transport layer film. The conductivity of spiro-OMeTAD doped with different tetrabutylammonium salt-stabilized free radicals and the relationship between the type of tetrabutylammonium salt stabilizer are shown in Figure 2. Figure 1 shown.
[0060] Among them, this embodiment sets up a total of seven groups of experiments, the blank group is numbered as group 10, relative to other groups, no free radical initiator and stabilizer are added, group 11 is relative to groups 12-16, only the free radical initiator benzoyl peroxide is added, and groups 12-16 are five groups in which free radical initiators are added and five tetrabutylammonium salt stabilizers are added respectively, wherein the molar ratio of the free radical initiator benzoyl peroxide to the organic semiconductor molecule is all 90 mol%, and the molar ratio of the added tetrabutylammonium salt stabilizer molecule to the organic semiconductor molecule is all 90 mol%. Other steps and conditions are the same as group 12; the specific group numbers and the conductivity of the obtained organic semiconductor film are shown in Table 1 below.
[0061] Table 1 Conductivity of organic semiconductor films doped with different tetrabutylammonium salt stabilizers
[0062]
[0063]
[0064] Depend on Figure 1 As shown in Table 1, compared with group 10 without adding free radical initiator and stabilizer, groups 11 to 16 can significantly improve the conductivity of organic semiconductor materials by adding free radical initiators and different stabilizers. 4 Order of magnitude, reaching 0.7×10 -4 ~3.0×10 -4 S cm -1 .
[0065] Example 2
[0066] Preparation of perovskite solar cells
[0067] Perovskite solar cells are a planar structure: FTO / tin dioxide / perovskite / doped spiro-OMeTAD / Au. The steps for preparing each functional layer are as follows:
[0068] (1) Femtosecond laser etching of transparent conductive substrate FTO glass, adding detergent to the surface of FTO glass, and using a wet non-woven fabric to clean the glass surface to remove residual particles on the surface. Then, ultrasonic cleaning was performed in detergent, deionized water, and anhydrous ethanol for 20 minutes each.
[0069] (2) Preparation of electron transport layer: Dissolve 1.096g of stannous chloride dihydrate, 100μL of thioglycolic acid, 5g of urea and 5mL of hydrochloric acid (37%) in 400mL of deionized water, shake well, and place the mixed solution in a refrigerator at 4°C for maturation. After 24h, the SnO2 mother solution can be obtained. Then, the mother solution can be diluted with deionized water in a volume ratio of (5:1) to obtain a clear SnO2 precursor solution. The cleaned FTO glass is immersed in a glass box containing 100mL of SnO2 precursor solution, sealed with plastic wrap, and reacted in an oven at 90°C for 2.5h. Rinse the substrate with deionized water three times until the solution becomes clear, and then ultrasonically clean it for 5min to remove the residual precursor solution on the surface. After drying, anneal on a hot plate at 180°C for 1h, and after cooling, a substrate with a SnO2 electron transport layer deposited is obtained.
[0070] (3) The perovskite light-absorbing layer was prepared by a one-step method. The perovskite precursor solution was a 1.4 M mixed lead salt consisting of 0.85 PbI2 and 0.15 PbBr2 and a 1.3 M organic cation consisting of 0.85 FAI and 0.15 MABr in a mixed solvent of N,N-dimethylformamide (DMF) / dimethyl sulfoxide (DMSO) (4:1, volume ratio). 34 μL of CsI (pre-dissolved in 2 M DMSO solution) was added to obtain the desired Cs 0.05 FA 0.79 MA 0.16 PbB 0.51 I 2.49 Perovskite precursor solution. Take 25 μL of the mixed perovskite solution and deposit the perovskite precursor evenly on the ozone-treated SnO2 substrate (UV irradiation for 15 min) at a speed of 6000 rpm and an acceleration of 1000 rpm / s. In the last 5 seconds, add 120 μL of anti-solvent ethyl acetate. After spin coating, anneal at 120 ° C for 45 minutes to obtain a perovskite layer.
[0071] (4) Hole transport layer: After the perovskite layer is cooled, spiro-OMeTAD is free radical doped to obtain an organic semiconductor solution C for the preparation of the hole transport layer. The organic semiconductor solution C is spin coated at a speed of 3000 rpm for 30 seconds, and the hole transport layer can be obtained by one-step spin coating.
[0072] In this embodiment, two groups of experiments, AB, were set up to investigate the effects of different amounts of free radical initiator and stabilizer, wherein benzoyl peroxide was used as the free radical initiator and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMIMTFSI) was used as the stabilizer; other steps and conditions were the same as those of group 12. Specific experimental group changes and parameters are shown in Table 2.
[0073] (5) The cell is attached to the mask plate, and a layer of 80nm Au electrode is evaporated on the hole transport layer by a high vacuum coating machine to obtain a complete perovskite solar cell. The effective area of the cell is 0.16cm 2 , the simulated sunlight intensity is 100mW cm -2 , that is, one sunlight.
[0074] Figure 2 (a) is a box plot of the cell efficiency distribution of the hole transport layer doped with different contents of free radical initiators; Figure 2 (b) is a box plot of the battery efficiency distribution prepared by adding 90 mol % free radical initiator and then adding different amounts of 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide (BMIMTFSI) as a stabilizer.
[0075] Table 2 Battery efficiency obtained with different amounts of free radical initiator and stabilizer
[0076]
[0077]
[0078] Note: Group 2A6 and Group 2B1 are two groups of experiments with the same conditions. The experimental results are slightly different, which is normal experimental fluctuation.
[0079] Depend on Figure 2 (a) and the data of Group 2A1 to Group 2A7 in Table 2 show that with the increase in the amount of free radical initiator benzoyl peroxide added, the photoelectric conversion efficiency shows a trend of first slowly increasing and then sharply decreasing. When a trace amount is added (5%-30mol%), the photoelectric conversion efficiency does not change significantly. Only when the addition amount reaches 60-90mol%, the photoelectric conversion efficiency is significantly improved. The performance is optimal when the molar ratio of free radical initiator to organic semiconductor is 90mol%. Figure 2 (b) and the data of Group 2B1 to Group 2B4 in Table 2 show that as the amount of stabilizer increases, the photoelectric conversion efficiency first increases rapidly and then decreases slowly. The performance of 1-butyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt as a stabilizer is optimal when the addition amount is 30 mol%. The average photoelectric conversion efficiency of the preferred embodiment of the present invention can reach 15.9 to 18.9%.
[0080] Therefore, preferably, the concentration of the free radical initiator benzoyl peroxide is 90 mol % and the concentration of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt is 30 mol %, and the device performance is optimal.
[0081] Figure 3The current density-voltage curve of the perovskite solar cell device doped with spiro-OMeTAD as the hole transport layer in this optimal solution. The results show that the cell photoelectric conversion efficiency is as high as 19.6%, with an open circuit voltage of 1.14V and a short circuit current density of 23.8mA cm -2 , the filling factor is 0.72.
[0082] Example 3
[0083] Femtosecond laser etching of transparent conductive substrate FTO glass, adding detergent to the surface of FTO glass, using a wet non-woven cloth to clean the glass surface to remove residual particles on the surface, and then ultrasonic cleaning in detergent, deionized water, and anhydrous ethanol for 20 minutes each.
[0084] Dissolve 1.096g of stannous chloride dihydrate, 100μL of thioglycolic acid, 5g of urea and 5mL of hydrochloric acid (37%) in 400mL of deionized water, shake well, and then place the mixed solution in a refrigerator at 4°C for aging. After 24h, the SnO2 mother liquor can be obtained. Then, the mother liquor can be diluted with deionized water in a volume ratio (5:1) to obtain a clear SnO2 precursor solution. The cleaned FTO glass is immersed in a glass box containing 100mL of SnO2 precursor solution, sealed with plastic wrap, and reacted in an oven at 90°C for 2.5h. Rinse the film three times with deionized water until the solution becomes clear, and then ultrasonically clean it for 5min to remove the residual precursor solution on the surface. After drying, anneal on a hot plate at 180°C for 1h, and after cooling, a substrate with a SnO2 electron transport layer deposited is obtained.
[0085] The perovskite light-absorbing layer was prepared by a one-step method. The perovskite precursor solution was a 1.4 M mixed lead salt composed of 0.85 PbI2 and 0.15 PbBr2 and a 1.3 M organic cation composed of 0.85 FAI and 0.15 MABr, which were dissolved in a N,N-dimethylformamide (DMF) / dimethyl sulfoxide (DMSO) (4:1, volume ratio) mixed solvent. 34 μL of CsI (pre-dissolved in 2 M DMSO solution) was added to obtain the required Cs 0.05 FA 0.79 MA 0.16 PbB 0.51 I 2.49 Perovskite precursor solution. Take 25 μL of the mixed perovskite solution and deposit the perovskite precursor evenly on the ozone-treated SnO2 substrate (UV irradiation for 15 min) at a speed of 6000 rpm and an acceleration of 1000 rpm / s. In the last 5 seconds, add 120 μL of anti-solvent ethyl acetate. After spin coating, anneal at 120 ° C for 45 minutes to obtain a perovskite layer.
[0086] After the perovskite layer is cooled, free radical doped spiro-OMeTAD is prepared as a hole transport layer. 90 mol% of free radical initiator benzoyl peroxide and 90 mol% of tetrabutylammonium hexafluorophosphate (TBAPF6) are added to the tetrachloroethane solution of spiro-OMeTAD, and the hole transport layer is obtained by spin coating at a speed of 3000 rpm for 30 seconds.
[0087] The battery is attached to the mask plate, and a layer of 80nm Au electrode is evaporated on the hole transport layer by a high vacuum coating machine to obtain a complete battery device.
[0088] The difference between Example 3 and Group 2B2 in Example 2 is the different types of stabilizers and the different amounts of stabilizers added. The performance of the battery devices prepared by the two are basically the same. Figure 4 The current density-voltage curve of the perovskite solar cell device doped with spiro-OMeTAD as the hole transport layer in this preferred embodiment. The results show that the photoelectric conversion efficiency of the perovskite solar cell prepared by adding 90 mol% tetrabutylammonium hexafluorophosphate is as high as 20.8%, with an open circuit voltage of 1.15 V and a short circuit current density of 23.3 mA cm -2 , the filling factor is 0.78. This indicates that the effects of adding 90 mol% tetrabutylammonium hexafluorophosphate and 30 mol% 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt are similar.
[0089] Comparative Example 1
[0090] When preparing the hole transport layer in Example 3, the following steps are used instead:
[0091] 73 mg of spiro-OMeTAD powder and 18 μL of 1.74 mol L -1 LiTFSI solution (pre-dissolved in acetonitrile), 29 μL of 0.2 mol L -1 FK209 solution (pre-dissolved in acetonitrile) and 30 μL tBP solution were dissolved in 1 mL of chlorobenzene solution, sealed and shaken to obtain a uniform spiro-OMeTAD precursor solution. Spin coating was performed at a speed of 3000 rpm for 30 seconds, and a hole transport layer was obtained by one-step spin coating. The rest of the preparation method was exactly the same as in Example 3 to obtain a comparative perovskite solar cell.
[0092] The unpackaged perovskite solar cells in Example 3 and Comparative Example 1 were placed in a nitrogen glove box and continuously tested at the maximum power point under an LED lamp simulating sunlight, with one point scanned every 30 minutes. Figure 5 MPP tracking output of unencapsulated perovskite solar cells under simulated one-sun illumination.
[0093] Depend on Figure 5 It can be seen that the battery based on free radical doped hole transport layer in Example 3 can maintain 70% of the initial efficiency within 200 hours, while the battery with conventional LiTFSI / O2 doped hole transport layer decays to 70% of the initial efficiency in about 100 hours. This indicates that the continuous working stability of the perovskite solar cell with free radical doped organic semiconductor as the hole transport layer in Example 3 is significantly higher than that in Comparative Example 1. Therefore, the novel method of free radical doping hole transport layer disclosed in the present invention is of great significance to promoting the commercialization process of perovskite solar cells.
[0094] In summary, the present invention relates to a free radical p-type doped organic semiconductor film and a preparation method thereof and its application in perovskite solar cells. This p-type doping method is to add a free radical initiator to a chlorinated organic solution of an organic semiconductor and mix them evenly; then add tetrabutylammonium salt or butyl-3-methylimidazolium salt to the solution as a stabilizer to obtain a stable p-type doped organic semiconductor solution; prepare the film by spin coating, scraping, slit coating and other methods and then dry it to obtain a solid-state free radical p-type doped organic semiconductor film. The doping method provided by the present invention is processed by solution, and the process is simple and controllable. The charge transfer capacity of the doped organic semiconductor is significantly improved. When applied to perovskite solar cells, the performance of the device, such as efficiency and stability, is significantly enhanced, and the photoelectric conversion efficiency reaches 15.9-20.8%.
[0095] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a free radical p-type doped organic semiconductor film, characterized in that: The following steps are involved: Adding a free radical initiator and a stabilizer to the first organic semiconductor solution in sequence and mixing them evenly to obtain a second organic semiconductor solution; wherein the first organic semiconductor solution is obtained by dissolving a p-type organic semiconductor in a chlorinated organic solvent; coating the second organic semiconductor solution on the substrate, drying it to form a film, and obtaining a free radical-based p-type doped organic semiconductor thin film; The free radical initiator is benzoyl peroxide or azobisisobutyronitrile; The stabilizer includes 30-90 mol% of tetrabutylammonium bistrifluoromethanesulfonyl imide or 10-60 mol% of butyl-3-methylimidazolium salt added relative to the p-type organic semiconductor, and the butyl-3-methylimidazolium salt is 1-butyl-3-methylimidazolium hexafluorophosphate or 1-butyl-3-methylimidazolium bistrifluoromethanesulfonyl imide.
2. The method for preparing a free radical p-type doped organic semiconductor thin film according to claim 1, characterized in that: The amount of the free radical initiator added relative to the p-type organic semiconductor is 5 to 120 mol %.
3. The method for preparing a free radical p-type doped organic semiconductor thin film according to claim 1, characterized in that: The p-type organic semiconductor is spiro-OMeTAD, P3HT, PTAA or poly-TPD.
4. The method for preparing a free radical p-type doped organic semiconductor thin film according to claim 1, characterized in that: The chlorinated organic solvent is tetrachloroethane or pentachloroethane.
5. The method for preparing a free radical p-type doped organic semiconductor thin film according to claim 1, characterized in that: The coating method is spin coating, blade coating or slot coating.
6. A free radical-based p-type doped organic semiconductor film obtained by the preparation method according to any one of claims 1 to 5.
7. A perovskite solar cell, characterized in that: The device structure of the perovskite solar cell is a cathode, an electron transport layer, a perovskite layer, a hole transport layer and a cathode arranged in sequence, and the free radical p-type doped organic semiconductor film according to claim 6 is used as the hole transport layer.